The RNA editor ADAR2 promotes immune cell trafficking by enhancing endothelial responses to interleukin-6 during sterile inflammation - Gatsiou, Aikaterini; Tual-Chalot, Simon; Napoli, Matteo; Ortega-Gomez, Almudena; Regen, Tommy; Badolia, Rachit; Cesarini, Valeriana; Garcia-Gonzalez, Claudia; Chevre, Raphael; Ciliberti, Giorgia; Silvestre-Roig, Carlos; Martini, Maurizio; et al. (Immunity, 2023)
Immune cell trafficking constitutes a fundamental component of immunological response to tissue injury, but the contribution of intrinsic RNA nucleotide modifications to this response remains elusive. We report that RNA editor ADAR2 exerts a tissue- and stress-specific regulation of endothelial responses to interleukin-6 (IL-6), which tightly controls leukocyte trafficking in IL-6-inflamed and ischemic tissues. Genetic ablation of ADAR2 from vascular endothelial cells diminished myeloid cell rolling and adhesion on vascular walls and reduced immune cell infiltration within ischemic tissues. ADAR2 was required in the endothelium for the expression of the IL-6 receptor subunit, IL-6 signal transducer (IL6ST; gp130), and subsequently, for IL-6 trans-signaling responses. ADAR2-induced adenosine-to-inosine RNA editing suppressed the Drosha-dependent primary microRNA processing, thereby overwriting the default endothelial transcriptional program to safeguard gp130 expression. This work demonstrates a role for ADAR2 epitranscriptional activity as a checkpoint in IL-6 trans-signaling and immune cell trafficking to sites of tissue injury.